Optimization of a recyclabe waste collection system: The Valorsul case study - Lopes, D. (2022)
This paper studies alternative scenarios for a recyclable waste collection system in order to increase efficiency in their operations. Three alternative scenarios are proposed where two different locations for one or two additional depots are studied. The problem is considered as a multi-depot vehicle routing problem and a solution approach is developed. The three scenarios are compared with the current solution regarding distance travelled, working hours, amount of waste collected and vehicle usage. Significant gains are obtained when depots are added to the current logistics system.